International survey of patients undergoing percutaneous coronary intervention and their attitudes toward pharmacogenetic testing. Issue 4 (June 2019) - Pereira, Naveen L.; So, Derek; Bae, Jang-Ho; Chavez, Ivan; Jeong, Myung Ho; Kim, Sang Wook; Madan, Mina; Graham, John; O'Cochlain, Fearghas; Pauley, Nicole; Lennon, Ryan J.; Bailey, Kent; et al.
Abstract : Objective: To evaluate perceptions toward pharmacogenetic testing of patients undergoing percutaneous coronary intervention (PCI) who are prescribed dual antiplatelet therapy (DAPT) and whether geographical differences in these perceptions exist. Participants and methods: TAILOR-PCI is the largest genotype-based cardiovascular clinical trial randomizing participants to conventional DAPT or prospective genotyping-guided DAPT. Enrolled patients completed surveys before and 6 months after randomization. Results: A total of 1327 patients completed baseline surveys of whom 28, 29, and 43% were from Korea, Canada and the USA, respectively. Most patients (77%) valued identifying pharmacogenetic variants; however, fewer Koreans (44%) as compared with Canadians (91%) and USA (89%) patients identified pharmacogenetics as being important ( P <0.001). After adjusting for age, sex, and country, those who were confident in their ability to understand genetic information were significantly more likely to value identifying pharmacogenetic variants (odds ratio: 30.0; 95% confidence interval: 20.5–43.8). Only 21% of Koreans, as opposed to 86 and 77% of patients in Canada and USA, respectively, were confident in their ability to understand genetic information ( P <0.001). Conclusion: Although genetically mediated clopidogrel resistance is more prevalent amongst Asians, Koreans undergoing PCI identified pharmacogenetic variants as less important to their healthcare, likely related to their lack of confidence in their ability to understand genetic information. To enable successful implementation of pharmacogenetic testing on a global scale, the possibility of international population differences in perceptions should be considered. Abstract : Supplemental Digital Content is available in the text.